2020
DOI: 10.1186/s12904-020-00603-3
|View full text |Cite
|
Sign up to set email alerts
|

Factors influencing GPs’ perception of specialised palliative homecare (SPHC) importance – results of a cross-sectional study

Abstract: Background: General Practitioners (GPs) are the main providers of primary palliative care (PPC). At the same time they are the main initiators of specialised palliative homecare (SPHC). In Germany, little is known about factors which influence GPs in their involvement of SPHC. Aim of our study is to identify factors that drive GPs to give value to and involve SPHC. Methods: A cross-sectional survey was performed. In 2018, questionnaires were mailed to 6000 randomly selected GPs from eight German federal states… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0
16

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 17 publications
(27 citation statements)
references
References 34 publications
0
11
0
16
Order By: Relevance
“…Für die jeweilige Entscheidung, ob AAPV oder SAPV zum Einsatz kommt, liegen Hinweise vor, dass diese in hohem Maße von den verfügbaren hausärztlichen AAPV-Kapazitäten abhängt [ 22 ]. Weitere Faktoren zur Erklärung regionalspezifischer Inanspruchnahmemuster sollen im Folgenden für ausgewählte KV-Regionen mit niedriger bzw.…”
Section: Diskussionunclassified
“…Für die jeweilige Entscheidung, ob AAPV oder SAPV zum Einsatz kommt, liegen Hinweise vor, dass diese in hohem Maße von den verfügbaren hausärztlichen AAPV-Kapazitäten abhängt [ 22 ]. Weitere Faktoren zur Erklärung regionalspezifischer Inanspruchnahmemuster sollen im Folgenden für ausgewählte KV-Regionen mit niedriger bzw.…”
Section: Diskussionunclassified
“…2 , 3 At the same time, it is evident that specialized palliative homecare does not only depend on the patient’s medical need (and demand) but also on surrounding factors that can impede the involvement of primary palliative care alone, such as the available palliative care infrastructure, as well as the high workload of general practitioners. 4 Therefore, it is valuable to compare the impact of primary palliative care and specialized palliative homecare in end-of-life care.…”
Section: Introductionmentioning
confidence: 99%
“…On the one hand, previous literature has shown that exercise interventions preserve physical function in prostate cancer patients with bone metastases. Compared with the control group, patients showed function improvements measured by PRO and functional tests after 3 months 32 . Specifically, 5 out of our 13 patients had bone metastasis in the femur.…”
Section: Discussionmentioning
confidence: 87%
“…On the other hand, to guarantee safety, exercise adaptations may have limited possible changes in muscle architecture, as a high load is required for a hypertrophic response 55 . In this regard, literature concerning exercise intervention in patients with bone metastases is quite limited to exercise feasibility, avoiding affected areas 32 or at low intensities 50 given the risk of fracture 56 . Another factor that may have influence changes in muscle mass is cancer treatment and cancer itself, as they induce muscular adaptations that counteract those induced by exercise training 57 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation